The role of linguistic context in conveying the syntactic meaning of the verb in Khanaqeen sub_dialec (Raparin Journal of Humanities (RJH), 2020)
In the first part, the researcher determined the personal pronouns in the dialect of Khanaqeen: one group of separate pronouns and two groups of attached pronouns. The position and function of each pronoun is explained. The second part deals with the theoretical aspect of verb formation. The relation between the lexical and syntactic structure of the verb is indicated. The study has revealed that the linguistic information of the verb is organized and accumulated in the lexical items. Later this linguistic information interacts to form the external syntactic structure of the verb within the frame of the phrase and sentences. The third part also deals with the role of linguistic context due to its central role in determining the tense of verbs and sentences in the dialect of Khanaqeen.